2004
DOI: 10.1177/104063870401600602
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pooling Sera on the Detection of Avian Pneumovirus Antibodies using an Enzyme-Linked Immunosorbent Assay Test

Abstract: Abstract. Pooling of samples is a cost-effective approach to estimate disease prevalence and to identify infected individuals. The objective of this study was to evaluate the use of serum pools for the detection of avian pneumovirus infection in turkey flocks by enzyme-linked immunosorbent assay, so that a minimum number of tests can be performed without compromising the sensitivity and specificity of the test. A total of 900 field samples were tested; 20 samples from each of 45 flocks. All samples were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The use of pooled samples allows testing of a large number of animals, reducing time and cost. However, a major limitation to using pools as diagnostic tools is the dilution of positive samples below the limit of detection, resulting in misdiagnosed false negatives [32,33]. Therefore, in the current study, the dilution effect when multiple samples are pooled was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The use of pooled samples allows testing of a large number of animals, reducing time and cost. However, a major limitation to using pools as diagnostic tools is the dilution of positive samples below the limit of detection, resulting in misdiagnosed false negatives [32,33]. Therefore, in the current study, the dilution effect when multiple samples are pooled was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…1). Previously, [21] had also showed that the dilution of serum (pools of three, four, five or seven) for the detection of avian pneumovirus antibodies using an enzyme-linked immunosorbent assay led to falsenegative results. Similarly, Chatterjee et al [38] investigated the detection of hepatitis B virus in human blood donors using nucleic acid testing (NAT), and found that the pooling of blood samples led to an increase in false-negative results, particularly for samples with a low virus load.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, diagnostic specificity and sensitivity depend on a number of factors, including inhibitory factors in the sample matrix, pool size and robustness of the assay [21][22], and each of these aspects need to be critically assessed. Therefore, in the present study, we evaluated the performance of the MT-PCR assay for the diagnosis of the two pathogenic genotypes (chitose and ikeda) of T. orientalis in cattle using individual and pooled blood samples.…”
Section: Introductionmentioning
confidence: 99%
“…Pooling samples allows for a larger number of samples to be tested quickly and more cheaply (Muñoz-Zanzi et al, 2000;Wells et al,2003;Maherchandani et al, 2004;Brinkhof et al, 2007) .However one of the greatest disadvantages of pooling samples is that it can result in a loss sensitivity of the diagnostic tests (Brinkhof et al, 2007). In the case of ELISA, the pooling of samples can also result in unacceptably high OD of samples which limits the amount of samples which can be tested together (Brinkhof et al, 2007).…”
Section: Discussionmentioning
confidence: 99%